The Effect of Governance on the Relationship Between Research and Development Expenditure and Economic Growth in South Africa - Clarietta Chagwiza; Emmanuel Owusu-Sekyere; Farai Kapfudzaruwa (Economies)
This study analyzes the effects of governance on the relationship between research and development expenditure and economic growth in South Africa using annual data from 1997 to 2022 using an autoregressive distributed lag (ARDL) model. The calculated F-tests for the two models in the ARDL bounds testing approach to cointegration revealed a long-run relationship between the series. In the model without a mediating factor, an insignificant impact of research and development (R&D) expenditure on economic growth is reported. However, when R&D interacted with governance, a positive and significant impact was observed. This implies that for R&D to have a positive impact on economic growth, there is a need for strong and quality governance to provide a conducive productive environment. Furthermore, given the ambiguous relationship between governance and economic growth, the Granger causality test results showed that governance granger-causes economic growth and not the other way round. The findings presented in this paper are expected to provide some useful insights for policymakers in South Africa and the African continent. The findings demonstrate the important role that governance plays in enhancing the developmental performance of critical macro-economic growth factors. The study potentially generates new dimensions (by including governance as a mediating factor) in the understanding of how the impact of R&D and other macroeconomic parameters on economic growth can be promoted.